A multi‐platform package for the analysis of intra‐ and interspecific trait evolution. Issue 11 (8th September 2020) - Gaboriau, Théo; Mendes, Fábio K.; Joly, Simon; Silvestro, Daniele; Salamin, Nicolas
Abstract: Evolutionary forces affect the distribution of phenotypes both within and among species. Yet, at the macro‐evolutionary scale, the evolution of intraspecific variance is rarely considered. Here, we present an r and a BEAST 2 implementation that extends the JIVE (Joint inter‐ and Intraspecific Variance Evolution) model aimed at the analysis of continuous trait evolution at both inter‐ and intraspecific level. Using a hierarchical Bayesian approach, we implemented a range of models for continuous trait evolution that operate independently on species means and variances along a phylogeny. The package uses Markov chain Monte Carlo for the inference of parameters and the evaluation of model fit. JIVE is available in the bite (Bayesian Integrative models of Trait Evolution) r package, as well as in BEAST 2. The two implementations offer the same continuous trait evolutionary models, but differ in their use and types of analyses. The r implementation allows for faster analyses by taking the phylogeny as data, while providing graphical and statistical functions as part of tools for model comparison, result parsing and summary, and plotting. In the BEAST 2 implementation, the species tree is a parameter, and both its topology and divergence times are jointly estimated with trait model parameters. The bite package and the BEAST 2 implementation introduce new frameworks within comparative phylogenetics that explicitly model intraspecific variance. These tools allow users to tackle long‐standing questions in evolutionary biology, such as the identification of key evolutionary processes determining niche conservatism, niche partitioning, and life‐history strategies.